Double-bounce domain-wall in Einstein-Yang-Mills-Scalar black holes - Mazharimousavi, S. Habib; Halilsoy, Mustafa; Tahamtan, Tayabeh (European Physical Journal C, Springer, 2013)
We find Einstein-Yang-Mills (EYM) black hole solutions endowed with massless scalar hair in the presence of a potential V(ϕ) as function of the scalar field ϕ. Choosing V(ϕ)=constant (or zero) sets the scalar field to vanish leaving us with the EYM black holes. Our class of black hole solutions is new so that they do not asymptote in general to any known limits. Particular case is given, however, which admits an asymptotically anti de Sitter limit in 6−dimensional spacetime. The role of the potential V(ϕ) in making double bounces (i.e. both a minimum and maximum radii) on a Domain Wall (DW) universe is highlighted.
The file in this item is the publisher version (published version) of the article.
Keywords: general relativity; black holes